Conceptualizing The Relation Between Turnover Intention and Quality of Work Life: An Empirical Investigation in Morocco - Oumaima BERGUIG; Noureddine ABDELBAKI (Communications of International Proceedings, 2022)
The objective of this study is to identify the quality of work life variables that affect employee turnover intention in Morocco. A literature review of papers studying the relationship between QWL and IT is conducted to model this relationship. The conceptual model is then empirically verified through data from a questionnaire provided to employees working in four industries in Morocco, namely the health, call center, information technology and journalism industries. Preliminary results are presented in this paper along with research perspectives.
Keywords: Quality of work life; Turnover intention; PLS approach.